8 Anterior tibial capsular avulsion: a possible cause of unexplained ankle pain in athletes. (20th December 2017) - Akhtar, MA; Bethapudi, S; Gower, A
Abstract : Ankle sprain is a common sports injury, which settles with rest, analgesia and physiotherapy. A small number of patients present late with persistent unexplained ankle pain. Magnetic resonance imaging (MRI) and ankle arthroscopy is used for diagnostics and therapeutic purposes. Our aim was to study the operative findings, outcomes and MRI findings of patients who had ankle arthroscopy for unexplained ankle pain in the last 2 years. A retrospective case notes review of 5 patients who had ankle arthroscopy under the care of a single Foot and ankle surgeon at the University Hospital of North Durham was conducted. The mean age was 34 years (range 19–44) for 3 female and 2 male patients. 3 patients played sport and reported to have previous ankle injury. The mean duration of symptoms was 71 months (range 19–240). Pre-operative MRI scan suspected an ATFL injury in 2 patients and 3 MRI scans were reported as Normal. Examination under anaesthesia showed a stable ankle and arthroscopic examination revealed anterior capsular detachment from tibia, which was debrided, and ankle joint was washed out in all patients. The mean follow up was 7 months (range 3–23). There were no postoperative complications. At last follow up 2 patients were discharged after complete resolution of symptoms while 3 patients had temporary relief. MRI Scans were reviewed again post operatively by a consultant radiologist and only one patient was found to have fluid filled pouching of the anterolateral ankle capsule. We believe that anterior capsular avulsion can result in unexplained ankle pain and should be carefully examined at ankle arthroscopy in patients with persistent, nonspecific ankle pain and a normal MRI scan.